2008
DOI: 10.1088/0022-3727/41/24/245408
|View full text |Cite
|
Sign up to set email alerts
|

Field-emission properties of the platinum coated SiO2nanowires synthesized by thermal evaporation method

Abstract: Silicon oxide (SiO2) nanowires were synthesized on a 3 cm × 3 cm Si wafer by thermal evaporation of Si@SiO2 core–shell particles under argon atmosphere at 1000 °C for 1 h. The SiO2 nanowires were of diameters ranging from 30 to 100 nm and the lengths were of several micrometres. The growth mechanism of SiO2 nanowires was studied and suggested to be a vapour–solid mechanism. Field-emission (FE) properties of the Pt coated SiO2 nanowires were studied and the result showed that a turn-on electric field of 2.9 V µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The β value is lower compared with the reported carbon nanotubes [30], ZnO nanowires [31], ZnS nanowires [32], SnO 2 nanowires [33], WO x nanowires [34,35], B nanowires [36,37], and LaB 6 nanowires [38], but is equivalent to the CdS nanostructure arrays [39] and Fe 2 O 3 columnar arrays [40]. Recently, Chiu et al [5] reported that there is no emission density from SiO 2 nanowires, but good FE properties from platinum coated SiO 2 nanowires. We also found that no FE properties can be found once the anode-sample distance goes beyond 30 μm, which may be due to the poor conductivity of the SiO 2 .…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…The β value is lower compared with the reported carbon nanotubes [30], ZnO nanowires [31], ZnS nanowires [32], SnO 2 nanowires [33], WO x nanowires [34,35], B nanowires [36,37], and LaB 6 nanowires [38], but is equivalent to the CdS nanostructure arrays [39] and Fe 2 O 3 columnar arrays [40]. Recently, Chiu et al [5] reported that there is no emission density from SiO 2 nanowires, but good FE properties from platinum coated SiO 2 nanowires. We also found that no FE properties can be found once the anode-sample distance goes beyond 30 μm, which may be due to the poor conductivity of the SiO 2 .…”
Section: Resultsmentioning
confidence: 82%
“…Recently, a variety of synthesis methods have been introduced, including chemical vapor deposition (CVD) [2,3], physical evaporation [4,5], sol-gel template method [6], carbon-assisted SiO x nanowire growth [7][8][9], laser ablation technique [10], and so on, to synthesize versatile structures of SiO 2 , such as nanowires, nanotubes, and regular spherical nanoparticles. Novel properties in the photoluminescence feature of stable ultraviolet (UV) emission and visible blue light from these SiO 2 nanowires have stimulated extensive interest, as it means that silica nanostructures could be utilized as promising photonic nanodevices (such as UV laser emitters ) [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, silica nanotubes have the characteristic of their room-temperature light-transmission properties in the visible range, and possible usage for hosting materials in bioanalysis and bioseparation and potential applications in optoelectronic nanodevices [2][3]. The SiO 2 -NTs can be fabricated by various approaches such as surfactant intercalation method, electroless deposition, sol-gel technique, templated-assistance method, MOCVD method and thermal evaporation method [4][5][6][7]. However, these techniques are less suitable for commercial applications because of the high cost of equipments, small-scale production, long processing time, and requiring working in an ultra-high vacuum.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon carbide (SiC) is a semiconducting material that possesses high thermal stability, good chemical resistivity, good mechanical strength, and unique optical properties. Many 1D SiC nanostructures such as nanorods 21 22 23 , nanowires 24 25 , nanotubes 26 27 , nanobelts 28 29 , and nanocables 30 31 32 have been synthesized. The field emission properties of such structures have been studied 33 34 .…”
mentioning
confidence: 99%